A Handoff Algorithm of Dynamic Decisions with Extenics for Wireless Cellular Networks. (9th March 2010) - Wu, Chen-Feng
Abstract : A traditional handoff algorithm always adopts stationary channel preservation schemes that cause the increase of call blocking probability (CBP) and the decrease of system utilization to reduce the call dropping probability (CDP) for handoff call. In this paper, the extension theory is introduced and applied to the handoff algorithm for participating handoff decisions and channel preservation. The mobile can perform handoff by predicting user mobility in advance based on extension-based derivation. By using the simple extension-based derivation, the required channels can be reserved for handoff call beforehand, and the required quality of service (QoS) is preserved during handoff occurring. Furthermore, both the QoS issue and the efficiency of channel allocation are considered simultaneously for the proposed algorithm. The extension and accumulation concepts are combined for reducing the number of guard channels in the proposed scheme, so the CBP does not reduce too much and the utilization of channel is more efficiency.